2008
DOI: 10.1182/blood.v112.11.2070.2070
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TOSO in CLL Is Triggered by B-Cell Receptor Signaling and Associated with Progressive Disease.

Abstract: Resistance towards apoptotic stimuli mediated by overexpression of antiapoptotic factors or extracellular survival signals like B-cell receptor stimulation (BCR) are considered to be responsible for accumulation of malignant B cells in CLL . TOSO, also known as Fas-inhibitory molecule 3 (FAIM3), was identified as overexpressed candidate gene in CLL based on re-evaluation of publicly available microarray data sets. Based on primary CLL samples from 106 patients, TOSO expression was compared to healthy donor B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Only patients without prior therapy or patients who had a period of at least 6 months since their last chemotherapy were included in this study. Fresh CLL samples were enriched by applying B‐RosetteSep (StemCell Technologies, Vancouver, BC, USA) and Ficoll‐ Hypaque (Seromed, Berlin, Germany) density gradient purification, resulting in purity of more than 98% of CD19/CD5 CLL cells (Pallasch et al , 2008a). Control cells were isolated from healthy blood donors using untouched depletion (naive B‐cell isolation kit II; Miltenyi, Bergisch‐Gladbach, Germany) resulting in at least 90% purity of B cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only patients without prior therapy or patients who had a period of at least 6 months since their last chemotherapy were included in this study. Fresh CLL samples were enriched by applying B‐RosetteSep (StemCell Technologies, Vancouver, BC, USA) and Ficoll‐ Hypaque (Seromed, Berlin, Germany) density gradient purification, resulting in purity of more than 98% of CD19/CD5 CLL cells (Pallasch et al , 2008a). Control cells were isolated from healthy blood donors using untouched depletion (naive B‐cell isolation kit II; Miltenyi, Bergisch‐Gladbach, Germany) resulting in at least 90% purity of B cells.…”
Section: Methodsmentioning
confidence: 99%
“…Control cells were isolated from healthy blood donors using untouched depletion (naive B‐cell isolation kit II; Miltenyi, Bergisch‐Gladbach, Germany) resulting in at least 90% purity of B cells. Isolated cells were cultured as previously described (Pallasch et al , 2008a, 2009). This study was approved by the ethics committee of the University of Cologne and blood samples were given with informed consent according to the Helsinki protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Control cells were isolated from healthy blood donors using untouched depletion (naive B‐cell isolation Kit II; Miltenyi, Bergisch‐Gladbach, Germany) resulting in at least 90% purity of B cells. Isolated cells were cultured as previously described 18, 19. This study was approved by the ethics committee of the University of Cologne; blood samples were given with informed consent according to the Helsinki protocol.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of cancer, FAIM3 was shown to be overexpressed in chronic lymphocytic leukemia (Proto-Siqueira et al 2008) and associated with disease progression (Pallasch et al 2008;Pallasch and Wendtner 2009). Protein and mRNA expression analyses demonstrated that high levels of FAIM3 expression were a unique feature of chronic lymphocytic leukemia cells and not present in other B-cell lymphomas (Pallasch and Wendtner 2009).…”
Section: Faim3mentioning
confidence: 99%